2014
DOI: 10.1155/2014/576039
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Model for the Transmission Dynamics of the Buruli Ulcer with Saturated Treatment

Abstract: The management of the Buruli ulcer (BU) in Africa is often accompanied by limited resources, delays in treatment, and macilent capacity in medical facilities. These challenges limit the number of infected individuals that access medical facilities. While most of the mathematical models with treatment assume a treatment function proportional to the number of infected individuals, in settings with such limitations, this assumption may not be valid. To capture these challenges, a mathematical model of the Buruli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Shi et al [49] proposed an HIV model with a saturated reverse function to describe the dynamics of infected cells. Additionally, Bonyah et al [50] developed a SIR model to study the dynamics of buruli ulcer and suggested policy measures to control the disease. Lastly, Zhang et al [51] developed a model with a latent period of the disease wherein the person is not infectious with saturated incidence rates and treatment functions, called SEIR epidemic model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shi et al [49] proposed an HIV model with a saturated reverse function to describe the dynamics of infected cells. Additionally, Bonyah et al [50] developed a SIR model to study the dynamics of buruli ulcer and suggested policy measures to control the disease. Lastly, Zhang et al [51] developed a model with a latent period of the disease wherein the person is not infectious with saturated incidence rates and treatment functions, called SEIR epidemic model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have linked MU positivity in the environment and water bugs with BU prevalence 8 18 , suggesting that MU positivity in water bugs can differentiate between endemic and non-endemic areas 18 , and that environmental MU positivity may predict BU prevalence spatially 8 . Other studies have explored the theoretical implications of these routes of transmission in mathematical models 31 . However, due to data limitations, no studies have considered the contribution of environmental pathways while controlling for potential water bug transmission or vice versa .…”
Section: Discussionmentioning
confidence: 99%
“…The third most prevalent mycobacterial disease in humans, Mycobacterium ulcerans (MU) infection leads to severe abnormalities and disability [1][2][3][4][5][6][7][8][9]. It is a member of the family of Mycobacteria that can affect both humans and animals with sickness [10,11].…”
Section: Introductionmentioning
confidence: 99%